Optimal Intensity for Oral Anticoagulation in Patients with Prosthetic Heart Valves - Turpie, Alexander G. G. (Hämostaseologie, 1997)
Antithrombotic therapy in patients with heart valve replacement has been placed on a firm scientific footing based on a number of prospective clinical trials. Patients with bioprostheses in the mitral position require a minimal of 3 months oral anticoagulants at a target INR of 2.0-3.0. Patients with bioprostheses with additional risk factors should receive oral anticoagulants indefinitely. Patients with mechanical prostheses require life-long anticoagulants at a target INR of 2.5-3.5. The addition of antiplatelet drugs to anticoagulants improves the outcome particularly in patients at risk of vascular disease.
Keywords: Prosthetic heart valve replacement; anticoagulant therapy; antiplatelet therapy; embolism; haemorrhage; clinical trials